2009
DOI: 10.1111/j.1365-2796.2009.02126.x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in auto‐immune haemolytic anaemia and immune thrombocytopenic purpura: a Belgian retrospective multicentric study

Abstract: This study confirms that rituximab induces responses in a majority of previously treated patients with AIHA and ITP. Response duration generally exceeds 1 year. Retreatment with rituximab in responding patients is most often successful. The outcome of patients who fail on rituximab is poor. We were not able to identify pretreatment patient characteristics predicting for response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 40 publications
6
61
0
6
Order By: Relevance
“…All patients remained in either CR or PR, at a mean follow-up of 604 days. Several retrospective studies in population of refractory primary or secondary AIHA confirmed the efficacy of rituximab [54][55][56][57][58][59]. The potential long-term complications of rituximab were reported by Carson et al [60], i.e., progressive multifocal leukoencephalopathy in two patients in 57 cases.…”
Section: Discussionmentioning
confidence: 90%
“…All patients remained in either CR or PR, at a mean follow-up of 604 days. Several retrospective studies in population of refractory primary or secondary AIHA confirmed the efficacy of rituximab [54][55][56][57][58][59]. The potential long-term complications of rituximab were reported by Carson et al [60], i.e., progressive multifocal leukoencephalopathy in two patients in 57 cases.…”
Section: Discussionmentioning
confidence: 90%
“…Recent reviews 31,32 reported that rituximab (375 mg/m 2 weekly for a median of 4 weeks) is effective in treating both warm AIHA and CAD, with a median response rate higher in the warm forms (overall response (OR) 83-87%, complete response (CR) 54-60% vs. OR 58%, CR 4.5%); disease free survival has been reported to be 72% at one and 56% at two years. 33 Rituximab has been shown to be effective both in idiopathic and secondary AIHA, including those associated with autoimmune and lymphoproliferative disorders, and bone marrow transplant. 31,32,[34][35][36][37] Responses to treatment were observed in monotherapy or in combination with corticosteroids, immunosuppressants and interferon-α, 35,36 and regardless of prior therapy.…”
Section: Rituximabmentioning
confidence: 99%
“…In this study, which had a very similar design as the study of Penalver et al, we reported on 53 patients with refractory AIHA treated with rituximab. Compared with the Spanish results overall response rates (79%) were similar, although the rate of complete responses (CR) was lower (47%) [2]. The reason for this difference is not clear as definition of CR and proportion of patients with cold type AIHA, a subtype in which the achievement of CR with rituximab monotherapy is rather rare, were similar [3].…”
Section: Dear Editormentioning
confidence: 86%
“…In our series nine patients were re-challenged with rituximab, leading to overall response characteristics similar to the responses achieved after the first course, including in some cases even longer response duration after rituximab re-treatment. In addition, one patient achieved a partial response although first rituximab course failed [2].…”
Section: Dear Editormentioning
confidence: 99%